Metformin versus chromium picolinate in clomiphene citrate-resistant patients with PCOs: A double-blind randomized clinical trial - Sedigheh Amooee; Mohammad Ebrahim Parsanezhad; Maryam Ravanbod Shirazi; Saeed Alborzi; Alamtaj Samsami (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Chromium picolinate could be effective in clomiphen citrate resistant PCOS patients. Objective: To compare the effects of chromium picolinate vs. metformin in clomiphen citrate resistant PCOS patients. Materials and Methods: The present randomized clinical trial was performed on 92 women with clomiphen citrate-resistant PCOS at the clinics which were affiliated to Shiraz University of Medical Sciences, Shiraz, Iran. The subjects were randomly assigned to two groups receiving either chromium picolinate (200μg daily) or metformin (1500mg daily) for 3 months. Anthropometric and hormonal profile were measured and compared both before and after the treatment. Ovulation and pregnancy rate was measured in the two study groups, as well. Results: Chromium picolinate significantly decreased fasting blood sugar (FBS) after 3 months of treatment (p=0.042). In the same way, the serum levels of fasting insulin had significantly decreased leading to an increase in insulin sensitivity as measured by QUICKI index (p=0.014). In comparison to the patients who received chromium picolinate, those who received metformin had significantly lower levels of testosterone (p=0.001) and free testosterone (p=0.001) after 3 months of treatment. Nevertheless, no significant difference was found between the two study groups regarding ovulation (p=0.417) and pregnancy rates (p=0.500). Conclusion: Chromium picolinate decreased FBS and insulin levels and, thus, increased insulin sensitivity in clomiphene citrate-resistance PCOS women. These effects were comparable with metformin; however, metformin treatment was associated with decreased hyperandrogenism. Overall, chromium picolinate was better tolerated compared to metformin; nonetheless, the two study groups were not significantly different regarding ovulation and pregnancy rates.